Microstructural Analysis of an LSCF Cathode Using In Situ Tomography and Simulation - Cooper,SJ; Kishimoto,M; Tariq,F; Bradley,RS; Marquis,AJ; Brandon,NP; Kilner,JA; Shearing,PR (ECS Transactions, 2013)
Electrode tortuosity factor is a key input parameter in many fuel cell simulations. Three-dimensional microstructural data obtained from in-situ synchrotron X-ray nano-computed tomography is used as the basis for comparing five approaches to quantify the tortuosity factor. Three of these techniques are based on diffusivity simulations and showed strong correlation, but had consistently different absolute values. A random walk method showed a good degree of correlation to the diffusive approaches, but had the largest values overall. Lastly, a calculation that used a mean pore centroid approach showed little correlation to any of the other three methods, but compared well with the conventional Bruggeman correlation. Due to the diffusive nature of the ionic transport in electrodes, the authors would recommend calculating tortuosity factors using a diffusive approach based on the voxels rather than a remeshed volume.